2014
DOI: 10.3389/fncel.2014.00430
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor: a bridge between inflammation and neuroplasticity

Abstract: Cytokines are key regulatory mediators involved in the host response to immunological challenges, but also play a critical role in the communication between the immune and the central nervous system. For this, their expression in both systems is under a tight regulatory control. However, pathological conditions may lead to an overproduction of pro-inflammatory cytokines that may have a detrimental impact on central nervous system. In particular, they may damage neuronal structure and function leading to defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
253
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(280 citation statements)
references
References 97 publications
7
253
1
5
Order By: Relevance
“…It has important functions in brain development and plasticityrelated processes and it is a crucial neuromodulator in central nociceptive hypersensitivity [230,231]. ATP-mediated increased expression and/or cellular release has been demonstrated for BDNF in a variety of cell types.…”
Section: Growth Factorsmentioning
confidence: 99%
“…It has important functions in brain development and plasticityrelated processes and it is a crucial neuromodulator in central nociceptive hypersensitivity [230,231]. ATP-mediated increased expression and/or cellular release has been demonstrated for BDNF in a variety of cell types.…”
Section: Growth Factorsmentioning
confidence: 99%
“…33 Future studies may analyze also the contribution of other factors, like brain-derived neurotrophic factor (BDNF) that was proposed as link between microglial activation and neuroplasticity. 36 On the other hand, a more differentiated view on microglia activation as potential therapeutic target ie, on the beneficial vs deleterious effects of minocycline is needed. We have to determine also the translational value of results obtained in the rodent model, before postulating cautiousness regarding the clinical use of tetracyclines.…”
mentioning
confidence: 99%
“…45,46 Previous research has shown that neurotrophins, as a bridge between the immune system and neuroplasticity, results from the integration of multiple mechanisms. 47 BCG vaccination has long been known to be a potent inducer of IFN-g-secreting Th1 responses and Tregs. 15,48,49 The increase in the levels of circulating immune factors (e.g., cytokines, chemokines or other factors), many of which can enter the CNS.…”
Section: Discussionmentioning
confidence: 99%